The non-viral vectors and main methods of loading siRNA onto the titanium implants and their application. Issue 16 (1st November 2020) - Chen, Liangrui; Bai, Mingxuan; Du, Ruiyu; Wang, Hao; Deng, Yi; Xiao, Anqi; Gan, Xueqi
Abstract: Surface modification of titanium implants by siRNA is quite efficient for improving implant osseointegration. Loading siRNA onto their surface is a crucial factor for siRNA-functionalized implants to realize their biological function. Direct binding of siRNA to implants has low siRNA binding and releasing rate, so usually it needs to be mediated by vectors. Polymeric, nonmaterial-mediated and lipid-based vectors are types of non-viral vectors which are commonly used for delivering siRNA. Three major methods of loading process, namely simple physical adsorption, layer-by-layer assembly and electrodeposition, are also summarized. A brief introduction, the basic principle and the general procedure of each method are included. The loading efficiency, which can be measured both qualitatively and quantitatively, together with gene knockdown efficiency, cytotoxicity assay and osteogenesis of the three methods are compared. A good many applications in osteogenesis have also been described in this review.